2001
DOI: 10.1023/a:1010668122693
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: From 1995 to 1999, four experiments were conducted on greenhouse roses to assess the effectiveness of the nC24 petroleum spray oil (PSO), D-C-Tron Plus, against two-spotted mite, Tetranychus urticae Koch (Acarina: Tetranychidae), and to determine how the oil could be most efficiently and effectively used in combination with the predatory mite Phytoseiulus persimilis Athias-Henriot (Acarina: Phytoseiidae) in an integrated pest management program. The results showed that 0.5% PSO applied fortnightly to roses gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In conclusion, it appears that the presence of sublethal quantities of AMO significantly changes the predation dynamics of the predatory mite P. persimilis in the presence of T. urticae, but in a way that is advantageous to techniques of integrated pest management, such as the partial spraying of plants as advocated by Nicetic et al (2001). P. persimilis would be even more effective if it had a strong aggregative response to high prey density in previously sprayed crops but further research is required to establish whether or not that is the case.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In conclusion, it appears that the presence of sublethal quantities of AMO significantly changes the predation dynamics of the predatory mite P. persimilis in the presence of T. urticae, but in a way that is advantageous to techniques of integrated pest management, such as the partial spraying of plants as advocated by Nicetic et al (2001). P. persimilis would be even more effective if it had a strong aggregative response to high prey density in previously sprayed crops but further research is required to establish whether or not that is the case.…”
Section: Discussionmentioning
confidence: 92%
“…If the lower parts of the plants are left as an unsprayed refuge, as suggested by Nicetic et al (2001), the mites must be tolerant of sublethal overspray reaching the refuge and also tolerant of sublethal residues when reinvading the previously sprayed parts of the plants and the predator must still be able to cause mortality to the pest.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were conducted on greenhouse roses to evaluate the efficacy of the nC24 petroleum spray oil (PSO), D-C-Tron in combination with Phytoseiulus persimilis (Acarina: Phytoseiidae) against Tetranychus urticae in the context of developing an integrated management program. Results showed that 0.5% PSO applied fortnightly to roses provided excellent protection against T. urticae infestation and did not affect the population density of P. persimilis in the upper and lower foliage [129]. In Brazil, on strawberry crops, control of T. urticae in the program based on release of Neoseiulus californicus (McGregor) and reduction of the frequency of acaricide applications (IPM) was effective in maintaining a significantly lower level of pest infestation, resulting in a six-fold reduction in the frequency of acaricide applications and, consequently, a reduction in selection pressure for acaricide resistance [130].…”
Section: Integrated Pest Management Of Tetranychus Urticaementioning
confidence: 97%
“…In front of us there is a wellknown monastery, the witness of devoted prayer and passionate love. "21…”
mentioning
confidence: 99%